2022
DOI: 10.1055/s-0042-1747685
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Cohort Analysis of Aspirin Use and Venous Thromboembolism in Patients with Pancreatic Cancer and an Indwelling Central Venous Catheter

Abstract: Background Patients with pancreatic cancer are at high risk of developing venous thromboembolism (VTE). It is unknown if aspirin reduces the risk of VTE in this setting. Objectives We sought to determine whether there is an association between aspirin use and VTE risk in patients with pancreatic cancer receiving chemotherapy with a central venous catheter (CVC). Patients/Methods We conducted a single-center, retrospective cohort study of adult patients diagnosed with pancreatic cancer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These findings were at odds with those of King et al (14) who claimed that cases who had ever taken aspirin had fewer VTE episodes than those who hadn't. While in another study Ahmed et al (15) showed that people using aspirin had a higher risk of developing VTE.…”
Section: Discussionmentioning
confidence: 62%
“…These findings were at odds with those of King et al (14) who claimed that cases who had ever taken aspirin had fewer VTE episodes than those who hadn't. While in another study Ahmed et al (15) showed that people using aspirin had a higher risk of developing VTE.…”
Section: Discussionmentioning
confidence: 62%
“…More than half of the patients included in this study were smokers, and a significant portion had comorbid conditions. Active smoking was previously associated with VTE events in patients with cancer [22].…”
Section: Discussionmentioning
confidence: 93%
“…For example, one study found that only 37% of patients prescribed LMWHs and 61% of patients prescribed oral agents were still continuing those treatments at 6 months [1]. In another study, it was shown that patients with any aspirin use had fewer VTE events (34.4%) compared to those without aspirin use [22]. In the study conducted by Akay et al, venous thrombosis in an upper extremity was commonly seen in cancer patients and treatment of DVT via DOACs was found to be more effective than LMWHs in preventing recurrent VTE (risk ratio: 0.111; 95% CI: 0.014-0.866) [35].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study of patients with PDAC treated with chemotherapy using a central venous catheter compared VTE incidence in 125 PDAC patients treated with aspirin to 189 patients with no aspirin treatment. 103 Patients treated with aspirin had fewer VTE events than patients not using aspirin (34 vs. 42%, p ¼ 0.021), while major bleeding and clinically relevant minor bleeding complication rates were similar. 103 Platelet aggregation inhibition (e.g., by aspirin treatment) might be an effective therapeutic strategy in the prevention of VTE in patients with PDAC, but a randomized clinical trial is required to evaluate this strategy.…”
Section: Plateletsmentioning
confidence: 90%
“…103 Patients treated with aspirin had fewer VTE events than patients not using aspirin (34 vs. 42%, p ¼ 0.021), while major bleeding and clinically relevant minor bleeding complication rates were similar. 103 Platelet aggregation inhibition (e.g., by aspirin treatment) might be an effective therapeutic strategy in the prevention of VTE in patients with PDAC, but a randomized clinical trial is required to evaluate this strategy.…”
Section: Plateletsmentioning
confidence: 90%